The Content of the Educational Component «Theory and Methods of Physical Education» in the Structure of Training Future Physical Education Teachers - Oleksandr Mozolev; Maryna Khmara; Volodymyr Mysiv (Pedagogical Discourse, 2025)
The article reveals the theoretical and practical components of the educational component «Theory and Methods of Physical Education» (TMPE) in the process of forming the professional training of future physical education teachers. The aim is to analyze the content of the educational component «TMPE» in the structure of general and special training of future physical education teachers at the Khmelnytsky Humanitarian-Pedagogical Academy. It has been established that TMPE is considered as an integrated discipline that provides theoretical and practical training of students and is one of the main disciplines in the structure of training of future physical education teachers. It includes teaching the following academic disciplines: 1) Introduction to the specialty; 2) Theoretical foundations of the system of physical education of schoolchildren; 3) Forms of organization of physical education classes in secondary education institutions; 4) Development of motor abilities of schoolchildren; 5) Methods of organizing and conducting physical education classes in the New Ukrainian School. TMPE has a theoretical, creative and practical component. The theoretical component of TMPE includes the study by students of general laws, principles, methods, forms and content of physical education, which allows reasonably managing the process of developing students' physical capabilities. The creative orientation of TMPE involves the preparation of coursework by students, which ensures the development of future specialists' creative abilities to organize and conduct search and research activities, and also promotes the development of innovative thinking in students. The practical orientation of TMPE is realized during practical classes and passing 7 types of practice. Conclusions. TMPE is a profiling discipline in the training of future physical education teachers. It integrates theoretical knowledge and practical skills, contributes to the formation of pedagogical, methodological, communicative and professional competencies of future teachers.